The Information Literacy as a fundamental element to the Education in Brazil - Capinzaiki Ottonicar, Selma Leticia [UNESP]; Silva, Rafaela Carolina [UNESP]; Baptista Belluzzo, Regina Celia [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2018)
Information literacy contributes to education, since individuals learn how to learn through specific knowledge, attitudes and experiences. As a result, they became competent to appropriate information quality and they aren't easily deceived by misinformation. A problem emerges in this context: How does information literacy can contribute to the education of Brazil? The purpose of this paper is to reflect about the importance of information literacy and its connection with education. The theme is important because some countries are committed to the New Agenda for 2030 which is focused on citizens' sustainable development. Furthermore, the paper establishes an interdisciplinary relationship between Information Science and Education. The methodological procedures are based on a bibliographical review about information literacy, education, lifelong learning and the current situation of education in Brazil. Belluzzo's standards and indicators (2007) were used because they are more appropriate in the Brazilian context. The conclusions illustrated that some information literacy models are used by several libraries, schools and universities around the world. However, the theoretical and practice researches are still in progress, so the information literacy investigation is fundamental to strengthen the education of Brazil.
Keywords: Brazil; Education; Information literacy; Lifelong learning